Transcriptional and Epigenetic Regulation of Monocyte and Macrophage Dysfunction by Chronic Alcohol Consumption - Malherbe, Delphine C.; Messaoudi, Ilhem (Frontiers in Immunology, 2022)
Drinking alcohol, even in moderation, can affect the immune system. Studies have shown disproportionate effects of alcohol on circulating and tissue-resident myeloid cells (granulocytes, monocytes, macrophages, dendritic cells). These cells orchestrate the body’s first line of defense against microbial challenges as well as maintain tissue homeostasis and repair. Alcohol’s effects on these cells is dependent on exposure pattern, with acute drinking dampening but chronic drinking enhancing production of inflammatory mediators. Although chronic drinking is associated with heightened inflammation, studies on tissue resident macrophage populations in several organs including the spleen, liver, brain, and lung have also shown compromised functional and metabolic capacities of these cells. Many of these effects are thought to be mediated by oxidative stress caused by alcohol and its metabolites which can directly impact the epigenetic cellular landscapes. In addition, since myeloid cells are relatively short-lived in circulation and are under constant repopulation from the bone marrow compartment, alcohol’s effects on bone marrow progenitors and hematopoiesis are important for understanding the impact of alcohol systemically on these myeloid populations. Alcohol-induced disruption of progenitor, circulating, and tissue resident myeloid populations contribute to the increased susceptibility of patients with alcohol use disorders to viral and bacterial infections.